Pengelolaan Program Kelompok Usaha Siswa (KUS) di SMA Negeri 5 Depok - Permana, Putut Said (Aufklarung: Jurnal Pendidikan, Sosial dan Humaniora, 2022)
This research aims to: (1) determine the management of the Kelompok Usaha Siswa (KUS) program at SMA Negeri 5 Depok; (2) identify the obstacles that occur in the management of the Kelompok Usaha Siswa (KUS) program at SMA Negeri 5 Depok. This research uses a qualitative approach. The research subjects consist of the KUS program managers and student participants in the KUS program at SMA Negeri 5 Depok. Research data was collected through observation and interviews. The data analysis technique uses the Miles and Huberman analysis model, namely data reduction, data display, and conclusion drawing. The results of this study indicate that: 1) the management of the KUS program at SMA Negeri 5 Depok has been carried out in accordance with general management functions, namely including planning, organizing, directing, and controlling. In its implementation, the management consists of the Curriculum Deputy Head, curriculum staff, and entrepreneurship subject teachers. 2) Obstacles in the implementation of the KUS program occur at the planning stage. This is due to the limitations of offline activities caused by the Covid-19 pandemic. The obstacles that arise are difficulties in scheduling the use of KUS program facilities. In the end, it was decided that not all students would use the facilities at school, only representatives of the groups were scheduled. This lasted until the permission for offline learning was officially issued by the government.